GOOD CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE: A CASE OF INDONESIAN CONSUMER GOODS INDUSTRY - Fedi Ameraldo (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2023)
The purpose of this study is to determine the effect of the board of directors, independent board of commissioners and audit committee on the financial performance of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2021. This study uses a quantitative approach with a population of 51 companies. The sample was taken using purposive sampling technique and obtained a sample of 44 companies. The data used in this study are secondary data. The analysis technique in this study uses multiple linear regression. The results of this study indicate that the independent board of commissioners has an effect on financial performance while the board of directors and audit committee have no effect on financial performance.